O Conceito de Direito Estatal Externo de G. W. F. Hegel (Revista Eletrônica Estudos Hegelianos, 2020)
The article aims to expose and analyze the Hegelian concept of ‘External State Right’ (äußere Staatsrecht), exposed and analyzed in §§ 330-340 of his Philosophy of Right (FD) and in § 547 of his Encyclopedia of Philosophical Sciences (ECF). The above mentioned §§, from a systematic point of view, are both in the 2nd subdivision (between ‘The Internal State Right’ [Das innere Staatsrecht] and ‘The World History’ [Die Weltgeschichte]) of ‘The State’ (Der Staat), which is the 3rd subdivision of ‘The Eticity’ (Die Sittlichkeit), which is the 3rd subdivision of ‘The Objective Spirit’ (Der objektive Geist) of Hegel’s cited works. This is a very important content and with several current and debatable aspects, especially the Hegelian concepts of ‘war’ and ‘peace’, such as when Hegel speaks of the ‘ethical moment of war’, including ‘a decision on war and peace’ and on ‘declaring war and peace and other treaties’, further discussing the Kantian concept of ‘perpetual peace’. Moreover, the Hegelian concept of Völkerrecht(translated ‘peoples right’, ‘gentium right’, ‘international right’) is essential, especially to try to mediate the always possible ‘conflict’ or ‘litigation of States’ and thus try to reach the ‘possibility of peace’. This is a research, exposition and critical-philological, historical and hermeneutical analysis of Hegel’s work, based on classical and interpretive Hegelian texts.